The effect of saline irrigation on selected soil properties, plant physiology and vegetative reproductive growth of Palsteyn appricots (Prunus armeniaca L.) - Volschenk, Theresa (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Soil Science))--University of Stellenbosch, 2005.